Strategy for Implementing Village Head Supervision by the Village Consultative Body for Transparency - Mukhammad Soleh; Wahyu Hindiawati; Vivi Sylvia Purborini (CV. RADJA PUBLIKA, 2026)
The duties of the Village Consultative Body (BPD) are regulated in Law Number 6 of 2014 concerning Villages, which include discussing and approving draft village regulations with the Village Head, accommodating community aspirations, and supervising the performance of the Village Head. This study aims to identify the factors that hinder the implementation of the BPD’s supervisory function toward the Village Head’s performance and to formulate strategies to overcome these obstacles in order to achieve transparent village governance. This research employed an empirical legal research method conducted in Asrikaton Village, Pakis District, Malang Regency. Data were obtained through interviews with village government officials and members of the Village Consultative Body, supported by relevant legal documents and literature studies. The findings indicate that the main obstacles in implementing supervision include weak coordination and communication between the village government and the BPD, limited professionalism and human resources of BPD members, insufficient operational budgets, and inadequate supporting infrastructure. To address these challenges, several strategies are proposed, including strengthening coordination and communication, improving the capacity and professionalism of BPD members through education and training, and increasing budgetary and infrastructural support for the BPD. These efforts are expected to enhance transparency, accountability, and democratic governance at the village level.